2019
DOI: 10.1590/1982-0216/201921612418
|View full text |Cite
|
Sign up to set email alerts
|

Effect of palatoplasty on speech, dental occlusion issues and upper dental arch in children and adolescents with cleft palate: an integrative literature review

Abstract: Purpose: to compile acquired knowledge related to speech, maxillary growth, dental arch and dental occlusion issues of subjects with cleft palate (associated or not with cleft lip), relating them to the found structural and morphological changes, along with time of surgery and surgical technique employed in palatoplasty. Methods: a search was carried out on four databases, namely: PubMed, SciELO, LILACS and MEDLINE, between May and August, 2018. The following descriptors, in Portuguese and in their correspond… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 14 publications
0
10
0
Order By: Relevance
“…A linear cephalometric analytic obtained by projecting straight lines from the A and B points, respectively, unto the functional occlusal plane at 90 • and measuring the horizontal distance form point AO to BO direction of the jaw utterly influenced by the earlier treatment protocol such as time and techniques of primary surgeries (7)(8)(9)(10)(11)(12). The detrimental effect of palatoplasty on sagittal growth of maxilla has been widely documented in literature (9) but whether cheiloplasty impedes the growth is still in controversy (8,13).…”
Section: Wits Appraisalmentioning
confidence: 99%
See 1 more Smart Citation
“…A linear cephalometric analytic obtained by projecting straight lines from the A and B points, respectively, unto the functional occlusal plane at 90 • and measuring the horizontal distance form point AO to BO direction of the jaw utterly influenced by the earlier treatment protocol such as time and techniques of primary surgeries (7)(8)(9)(10)(11)(12). The detrimental effect of palatoplasty on sagittal growth of maxilla has been widely documented in literature (9) but whether cheiloplasty impedes the growth is still in controversy (8,13).…”
Section: Wits Appraisalmentioning
confidence: 99%
“…Atypical sagittal growth of maxilla is a common manifestation in patients with UCLP; acknowledged by many researchers yet all of them came to an understanding that the growth and direction of the jaw utterly influenced by the earlier treatment protocol such as time and techniques of primary surgeries ( 7 12 ). The detrimental effect of palatoplasty on sagittal growth of maxilla has been widely documented in literature ( 9 ) but whether cheiloplasty impedes the growth is still in controversy ( 8 , 13 ). A number of researchers found that cheiloplasty has an effect on maxillary incisors, alveolar bone and development of maxilla as well whether some researchers claimed no effect on maxillary development ( 7 , 11 , 12 , 14 , 15 ).…”
Section: Introductionmentioning
confidence: 99%
“…A series of surgeries is aimed at the treatment of this congenital anomaly for the correction of esthetic and functional development. The manifestation of undeveloped maxillary growth and occurrence of Class III malocclusion is frequent in UCLP patients ( 6 , 7 ). The growth and development of the maxilla are affected by different techniques of primary lip and palate surgeries.…”
Section: Introductionmentioning
confidence: 99%
“…Subjects with CLP must be submitted to surgical procedures to repair the lips (lip repair surgery), the palate (palatoplasty), or both while still a baby to favor oral functions 5,6 . The age when these procedures take place can influence these subjects' speech acquisition process, as well as the conformation of the upper dental arch and the transversal and anteroposterior measurements of the maxilla [6][7][8] . Palatoplasty is considered early between 12 and 18 months, and lip repair, between 3 and 6 months, according to the Craniofacial Anomalies and Rehabilitation Hospital of the Universidade de São Paulo (University of São Paulo) 9 .…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, it restricts the anterior growth of the maxillary arch 10 . Early palatoplasty favors a better speech profile 11 , although it can inhibit the maxillary growth, with consequences to dental occlusion 7,11 .…”
Section: Introductionmentioning
confidence: 99%